Where the Big Bucks Will Come From: Implementing Product Line Engineering for Railway Rolling Stock. Issue 2 (21st August 2019) - Chalé Góngora, Hugo Guillermo; Greugny, François
ABSTRACT: This paper presents a mid‐term return of experience from Alstom's rolling stock division on its implementation of product line engineering (PLE). It describes the journey we have undertaken to implement PLE, the challenges we have had to face, and the manner in which we are finding our way (most of the time deliberately, sometimes fortuitously) to define a profitable reuse strategy and to structure our approach on PLE. The paper also presents some encouraging intermediate results and concludes with the perspectives and the future challenges in our search for product line systems engineering excellence.